MODEL PELAYANAN PEMERINTAH DAERAH YANG MEMUASKAN PELANGGAN INTERNAL DAN EKSTERNAL BERBASIS TOTAL QUALITY MANAGEMENT - Dasman Lanin; Syamsir Syamsir; Boni Saputra (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
Simultaneously, service quality as measured by customer satisfaction (internal and external) has not been the focus of service improvement in Indonesia, the new Menpan and Bureaucratic Reform measure the Community Satisfaction Index (IKM) for external customers. In this study, equity theory is assumed to be a bridge between internal and external customer satisfaction. This study analyzes the level of differences in internal and external customer satisfaction on service transactions and analyzes the effect of internal customer satisfaction on service transactions and the effect of service transactions on external customer satisfaction. Service transactions use indicators of delivery, timeliness, information, professionalism, staff attitudes, and organizational politics. The final objective of this research is to create a quality local government service model through the Total Quality Management (TQM) approach. This research was conducted at RSUD Padang Panjang using an asocial quantitative approach. Data collection used a Likert scale questionnaire which had previously been tested for validation and reliability both in content and in empirical test items. A valid and reliable questionnaire was then used to collect data samples taken using stratified proportional random sampling technique, using the Slovin formula (error 2%) obtained a sample of 201 internal respondents and 956 external respondents. Data were analyzed by regression and t-test that had previously been tested classical assumptions. The results showed that there is a significant effect of internal customer satisfaction on service transactions and the effect of service transactions on external customer satisfaction. While the t-test results emphasize the level of significant differences in information and indicators of organizational politics.